2011
DOI: 10.5402/2011/201529
|View full text |Cite
|
Sign up to set email alerts
|

Acalculous Cholecystitis in a Patient with Hepatocellular Carcinoma on Sorafenib

Abstract: A 67-year-old woman with compensated cirrhosis type B associated with hepatocellular carcinoma was started on sorafenib for multiple pulmonary metastases. The patient developed right upper quadrant pain and high fever 4 weeks later. Imaging revealed marked enlargement of the gallbladder without calculi. Following percutaneous transhepatic gallbladder aspiration, her symptoms resolved, but the gallbladder remained enlarged. Laparoscopic cholecystectomy was performed. Arteriolar occlusion with intimal thickening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Of note, the patient had received treatment with multiple TKIs for a long time, so long-term treatment with TKIs might have induced the gallbladder perforation. However, previous reports (8)(9)(10)(11)(12) showed that cholecystitis developed about four weeks after initiating TKIs. These findings suggest that TKI-related cholecystitis developed after a relatively short treatment duration.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Of note, the patient had received treatment with multiple TKIs for a long time, so long-term treatment with TKIs might have induced the gallbladder perforation. However, previous reports (8)(9)(10)(11)(12) showed that cholecystitis developed about four weeks after initiating TKIs. These findings suggest that TKI-related cholecystitis developed after a relatively short treatment duration.…”
Section: Discussionmentioning
confidence: 93%
“…In patients with thyroid cancer treated with lenvatinib, five cases of acalculous cholecystitis were reported in post-marketing surveillance from 2015 to 2017 in Japan. In contrast, five cases of acute acalculous cholecystitis in patients treated with other tyrosine kinase inhibitors (TKIs) were reported, including two patients with sorafenib and three with sunitinib (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the blockage exerted on the VEGF signaling pathway can ultimately result in an increased platelet activation and arterial thromboembolism via the reduction of prostaglandin I-2 and nitric oxide [17]. The arteriolar thrombosis in gallbladder could lead to ischemia and acalculous AC, as documented in a patient with HCC treated with sorafenib [18]. Furthermore, since cholangiocytes express VEGFR-2 and VEGFR-3 and secrete VEGF which has an important role in inducing their proliferation in response to cholestasis [19], drugs inhibiting VEGF-R are predicted to cause biliary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of gallbladder toxicity is uncertain, although such toxicity has also been reported for others TKIs. 8-10 There is clear evidence that VEGF plays a role in modulating cholangiocyte proliferation in response to cholestasis and that cholangiocytes express VEGFR. 11 Inhibition of VEGFR in biliary tract cells can represent an imbalance of stress adaption, causing biliary diseases.…”
Section: Discussionmentioning
confidence: 99%